2019
DOI: 10.1101/547331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aversive learning strengthens episodic memory in both adolescents and adults

Abstract: 32Adolescence is often filled with positive and negative emotional experiences that may change 33 how individuals remember and respond to stimuli in their environment. In adults, aversive 34 events can both enhance memory for associated stimuli as well as generalize to enhance 35 memory for unreinforced but conceptually related stimuli. The present study tested whether 36 learned aversive associations similarly lead to better memory and generalization across a 37 category of stimuli in adolescents. Participant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In one such study, adolescents demonstrated greater reward-based modulation of hippocampal-striatal connectivity than adults, and the strength of this connectivity predicted reward-related memory (Davidow et al, 2016). However, other studies have not found evidence for developmental change in the influence of valenced outcomes on memory (A. O. Cohen et al, 2019; Katzman & Hartley, 2020).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In one such study, adolescents demonstrated greater reward-based modulation of hippocampal-striatal connectivity than adults, and the strength of this connectivity predicted reward-related memory (Davidow et al, 2016). However, other studies have not found evidence for developmental change in the influence of valenced outcomes on memory (A. O. Cohen et al, 2019; Katzman & Hartley, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…However, other studies have not found evidence for developmental change in the influence of valenced outcomes on memory (A. O. Cohen et al, 2019; Katzman & Hartley, 2020). The influence of different motivational and reward signals on memory across development may not be straightforward — individual and developmental differences in neurocognitive processes including sensitivity to valenced feedback (Ngo et al, 2019; Rosenbaum et al, 2020), curiosity (Fandakova & Gruber, 2021), and emotional processing (Adelman & Estes, 2013; Eich & Castel, 2016) may interact, leading to complex relations between age, motivation, and memory performance.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the type of information which different ages attend to may influence working memory and what information is subsequently retained (Blanco & Sloutsky, 2019;Deng & Sloutsky, 2016;Plebanek & Sloutsky, 2017). During adolescence there is evidence of enhanced attention and memory for reinforced, rewarded and threat-related information during adolescence (Cohen et al, 2019(Cohen et al, , 2021Cohen-Gilbert & Thomas, 2013;Davidow et al, 2016;Grose-Fifer et al, 2013;Meyer & Pattwell, 2020;Pattwell et al, 2012) and a preference for novelty (Galvan, 2010;Spear, 2013). Together these findings suggest that developmental patterns in working memory performance and subsequent recognition memory may be influenced by task demands and features of the stimuli (e.g., complexity, relevance, salience, novelty).…”
Section: Introductionmentioning
confidence: 99%